2022
DOI: 10.1002/cl2.1225
|View full text |Cite
|
Sign up to set email alerts
|

Interventions designed to improve financial capability: A systematic review

Abstract: Background There is growing recognition that people need stronger financial capability to avoid and recover from financial difficulties and poverty. Researchers are testing financial capability interventions with adults, children, immigrant populations and other groups, but little is known about the effectiveness of financial capability interventions on financial behaviour and financial outcomes. Objectives The purpose of this review is to inform practice and policy by examining and synthesizing evidence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 83 publications
(407 reference statements)
1
10
0
Order By: Relevance
“…As seen in Figure 1, the search resulted in 35,484 possibly eligible citations. After excluding duplicates, non-relevant and ineligible reports (Birkenmaier et al, 2022) Appendix D), 24 unique studies (i.e., used unique samples) are included in this review. Six of those 24 unique studies were large longitudinal studies that presented unique analyses in sub-studies that used different time points, subsamples, and/or outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As seen in Figure 1, the search resulted in 35,484 possibly eligible citations. After excluding duplicates, non-relevant and ineligible reports (Birkenmaier et al, 2022) Appendix D), 24 unique studies (i.e., used unique samples) are included in this review. Six of those 24 unique studies were large longitudinal studies that presented unique analyses in sub-studies that used different time points, subsamples, and/or outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we extracted data from 48 reports (including summary reports), and report data and analyses from 24 unique studies. Detailed results information is available from the final report published by the Campbell Collaboration (Birkenmaier et al, 2022) .
Figure 1.Study Screening Process. Review of 35,484 titles/ abstracts for potential studies found in search process.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations